Pengaruh Kualitas Produk, Harga dan E-Wom Terhadap Keputusan Pembelian Barang Elektronik Melalui Platform Tokopedia - Wahyuni, Ni Putu Eka; Suputra, Gusti Alit; M. Arsha, I Made Risma (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This study examines how e-Women, pricing, and product quality influence digital marketing purchases. This research includes 726,800 Denpasar residents who have never bought Tokopedia products. Purposeful sampling and linear regression analysis were employed to test 200 samples. Consumer purchase decisions are significantly and somewhat positively influenced by pricing, e-commerce, and product quality. Cost, quality, and affordability all influence what people decide to buy. Based on what the study found, Tokopedia should constantly be adding new products to its inventory to pique customers' interest in visiting its online store. Tokopedia is expected to display products on the Tokopedia application according to the actual condition of the goods. Tokopedia should be able to re-evaluate the prices it offers, so that it can be more competitive than competitors. Tokopedia should be able to provide answers to every consumer question regarding the products purchased by consumers.